2020
DOI: 10.1371/journal.pone.0236156
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of HIV drug resistance among antiretroviral treatment (ART) experienced adolescents and young adults living with HIV in Ndola, Zambia

Abstract: Background HIV drug resistance (HIVDR) poses a threat to the HIV epidemic control in Zambia especially in sub-populations such as the 15-24 years where there is poor virological suppression. Understanding the prevalence and patterns of HIVDR in this population (15-24 years) will contribute to defining effective antiretroviral therapy (ART) regimens, improving clinical decision making, and supporting behavioral change interventions needed to achieve HIV epidemic control. Methods A cross-sectional analysis of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Now an effectiveness trial Pilot, Randomized controlled trial, crossover secondary Depression; Emotional regulation; trauma; substance misuse PHQ9, SDQ, UCLA Trauma RI Project YES! Youth Engaging for Success ClinicalTrials.gov Identifier: NCT04115813 Zambia [ 87 92 ] AHISA Clinic/hospital Test the impact of a theory-based intervention that utilizes trained and paid HIV-positive youth peer mentors (YPMs) to deliver the intervention consisting of monthly one-on-one and small group sessions with AYA, ages 15 to 24 years. Optional caregiver support groups are incorporated.…”
Section: Resultsmentioning
confidence: 99%
“…Now an effectiveness trial Pilot, Randomized controlled trial, crossover secondary Depression; Emotional regulation; trauma; substance misuse PHQ9, SDQ, UCLA Trauma RI Project YES! Youth Engaging for Success ClinicalTrials.gov Identifier: NCT04115813 Zambia [ 87 92 ] AHISA Clinic/hospital Test the impact of a theory-based intervention that utilizes trained and paid HIV-positive youth peer mentors (YPMs) to deliver the intervention consisting of monthly one-on-one and small group sessions with AYA, ages 15 to 24 years. Optional caregiver support groups are incorporated.…”
Section: Resultsmentioning
confidence: 99%
“…Although they did not analyze the prevalence of doravirine resistance, the high prevalence of Y188 C/L mutations (36.2%) conferred high-level resistance to doravirine according the Stanford University HIV db Program (HIV db version 9, last updated on 2021-02-22) 14 .A possible reason could be related to cross-resistance with nevirapine and efavirenz, which are widely used as first-line ART and prevention of mother-to-child transmission (PMTCT) programs. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there were relatively high prevalence rates of the NNRTI mutations V106A (36.2%), Y188C/L (36.2%) and P225H (20.7%), which conferred resistance to etravirine. Although they did not analyze the prevalence of doravirine resistance, the high prevalence of Y188 C/L mutations (36.2%) conferred high-level resistance to doravirine according the Stanford University HIV db Program (HIV db version 9, last updated on 2021-02-22) 14 .A possible reason could be 17 In a study conducted in South Africa, Steegen et al reported rates of predicted intermediate and high-level resistance of 41% and 43.8% to doravirine, respectively, among 1372 patients who failed NNRTI-based ART when using the less stringent Stanford HIVdb v8.9 resistance interpretation criteria 9 (in which the V106I mutation was considered to confer resistance) compared to the Stanford HIVdb v9.0 criteria. However, none of the aforementioned studies reported on how many patients used STRs.…”
Section: Dovepressmentioning
confidence: 99%
“…study procedures relied on the results of only one viral load test; if a viral load was ≥1000 copies/mL, a resistance test was done to determine whether participants were on an effective HIV drug regimen. The study’s data on resistance testing was among the evidence considered in development of Zambia’s revised guidelines, published in 2020 [ 33 ]. Resistance testing is now recommended for all patients switching to a second line drug after two viral load tests indicate viral failure, and adherence issues are addressed [ 34 ].…”
Section: Discussionmentioning
confidence: 99%